PENGUATAN LEGAL AWARENESS DAN ECONOMIC LITERACY BAGI PELAKU USAHA MIKRO DI DESA KOLOWA - La Ode Dedi Abdullah; Endang Tri Pratiwi (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Based on the results of normative research, it can be concluded that (1) the application of legal awareness and economic literacy for micro-business actors in Kolowa Village shows that despite having great economic potential, business legal awareness is still low and economic literacy is only at the basic-intermediate level, with limitations in financial management and planning. These two aspects are interconnected and play an important role in opening access to capital, markets, and business protection but are still constrained by limited information and mentoring. Therefore, integrated and sustainable legal and economic education programs are needed to support the sustainability and competitiveness of microenterprises. (2) Research results in Kolowa Village show that strengthening legal awareness and economic literacy among microentrepreneurs is still hampered by limited access to information and infrastructure, cultural resistance, low managerial capacity, weak sustainable mentoring, and a lack of coordination among village institutions. This impacts legal certainty, economic resilience, and business competitiveness, necessitating an integrated and sustainable approach that combines legal and economic education with practical mentoring based on the village ecosystem.